Differences in PJBL Model With PBL on Self-Efficacy of Grade V Elementary School Students - Budi Setiawan; Farida F (International Journal of Educational Dynamics, 2019)
The study aims to reveal the differences in the Project Based Learning Model with the Problem Based Learning Model of Self Efficacy in fifth grade students of SD Kartika 1-11 Padang Timur District. The type of research used is quasi experiment with the design of the static group comparison design. The population in this study were all fifth grade students of SD Kartika 1-11 Padang TImur District with sample VE class as experimental class 1 and VE as experimental class 2. Sampling was done by probability sampling technique with the type of proportionate stratified random sampling. Data analysis techniques through the students' pretest and posttest Self Efficacy abilities. The hypothesis is proposed using the t test formula. The results showed that there were differences in the Self Efficacy of students in the experimental group 1 who took science learning using the Project Based Learning model for the experimental group 2 students taking science learning using the Problem Based Learning model with the average Self Efficacy questionnaire in the experimental class 1 at 72.92 posttes 87.58 and the average Self Efficacy questionnaire for the experimental class 2 students was pretest 63.13 posttest 71.04.